2008
DOI: 10.1159/000180313
|View full text |Cite
|
Sign up to set email alerts
|

Restless Legs Syndrome Is Common among Female Patients with Fibromyalgia

Abstract: Background: The prevalence of restless legs syndrome (RLS) among the general population is 2–15%, and with fibromyalgia syndrome (FMS) 2%. Both RLS and FMS are more common among women. The aim of our study was to evaluate the prevalence of RLS in a group of female patients diagnosed with FMS and to compare the occurrence of symptoms of daytime sleepiness and experienced sleep disorders between fibromyalgia patients with or without RLS. Method: Three hundred and thirty-two female patients, 20–60 years old, diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 52 publications
6
39
0
4
Order By: Relevance
“…The presence of RLS in patients with FM was investigated previously, but the presence of FM has not been studied in patients with RLS. Stehlik et al (44) reported that the presence of FM in patients with RLS might be lower. In our study, FM prevalence was high in patients with RLS (36.67%) and was significantly higher (5 times) than that of the control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of RLS in patients with FM was investigated previously, but the presence of FM has not been studied in patients with RLS. Stehlik et al (44) reported that the presence of FM in patients with RLS might be lower. In our study, FM prevalence was high in patients with RLS (36.67%) and was significantly higher (5 times) than that of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of RLS in studies in patients with FM was found as 65% (9,38). Although both diseases are known to be associated, differential diagnosis might be difficult in patients with severe pain in the lower extremities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopaminergic abnormalities have been hypothesized in the aetiology of RLS. 26 Stehlik et al 6 found that 64% of patients diagnosed with FMS (a rheumatological and chronic pain condition) were also affected by RLS, and FMS prevalence is markedly increased in patients with BD. 11 It has been postulated that FMS and RLS may possess a similar pathophysiology, such as a dysfunction of the CNS dopaminergic system.…”
Section: Discussionmentioning
confidence: 99%
“…11 It has been postulated that FMS and RLS may possess a similar pathophysiology, such as a dysfunction of the CNS dopaminergic system. 6 In addition, Wood et al 27 recently used positron emission tomography to demonstrate that FMS patients have an abnormal dopamine response to pain. Dopaminergic cells have been found to have potentially nociceptive functional capacity, 28 -30 and CNS involvement in BD may result in a dysfunction of the CNS dopaminergic system.…”
Section: Discussionmentioning
confidence: 99%